VIDEO-LAPAROSCOPIC ESOPHAGEAL MUCOSECTOMY IN ADVANCED IDIOPATHIC MEGAESOPHAGUS: A CASE REPORT - Chaib, Paulo Sergio; Tedrus, Gloria Maria; Aquino, Jose Luiz Braga; Mendonça, Jose Alexandre (Seven Editora, 2025)
Introduction: Advanced idiopathic megaesophagus is a condition with high morbidity and mortality, whose type of surgical procedure is still controversial. Case report: A 41-year-old patient with a clinical history of advanced megaesophagus (stage IV), onset 4 years ago, confirmed by clinical, radiological, and manometric parameters. The patient underwent laparoscopic esophageal mucosectomy by the abdominal approach combined with cervicotomy, without complications and with good recovery in the immediate postoperative period, and without complications after one year of follow-up. Conclusion: Laparoscopic esophageal mucosectomy proved to be a good surgical technique option for advanced idiopathic megaesophagus, with low morbidity in the immediate postoperative period and after one year of follow-up.DOI: https://doi.org/10.56238/sevened2025.028-007